2023
DOI: 10.3390/d15091006
|View full text |Cite
|
Sign up to set email alerts
|

The Diversity of Arbuscular Mycorrhizal Fungi and Their Associations in South America: A Case Study of Argentinean and Brazilian Cattle Raising Productive Ecosystems: A Review

Mónica A. Lugo,
Roberto Emanuel Ontivero,
Hebe J. Iriarte
et al.

Abstract: Mycorrhizal fungus diversity is an ecosystem health indicator, and thus, the appreciation of the aboveground as well as the belowground biota, such as fungi associated with natural and managed ecosystems, is essential to provide sustainable products and suggestions to farmers. Less is known about the totally arbuscular mycorrhizal fungi (AMF) and fungal endophytes useful to agroecology, which are environment friendly microbial biofertilizers to mitigate the complications of conventional farming. Specific AMF a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 144 publications
(228 reference statements)
0
1
0
Order By: Relevance
“…observ.) and Brazil (Lugo et al, 2023 ). Bayesian inference and ML analyses of sequences deposited in GenBank showed that no sequence with >96% identity to the A. gedanensis 45S sequences clustered with this species (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…observ.) and Brazil (Lugo et al, 2023 ). Bayesian inference and ML analyses of sequences deposited in GenBank showed that no sequence with >96% identity to the A. gedanensis 45S sequences clustered with this species (data not shown).…”
Section: Resultsmentioning
confidence: 99%